Comparison of the EQ-5D 3L and the SF-6D (SF-36) contemporaneous utility scores in patients with chronic kidney disease in Sri Lanka: a cross-sectional survey. Issue 2 (15th February 2019) - Kularatna, Sanjeewa; Senanayake, Sameera; Gunawardena, Nalika; Graves, Nicholas
Abstract : Objectives: The aim of this study was to compare utility weights of EuroQoL-five-dimension-3 levels (EQ-5D-3L) and Short-Form six-dimension (SF-6D) in a representative cohort of patients with chronic kidney disease (CKD). A cost–utility analysis (CUA) is designed to report the change to costs required to achieve an estimated change to quality-adjusted life years (QALYs). The quality component of a QALY is measured by utility. Utility represents the preference of general population for a given health state. Classification systems of the multi-attribute utility instruments (MAUIs) are used to define these health states. Utility weights developed from different classification systems can vary and may affect the conclusions from CUAs. Design: A community-based cross-sectional study. Setting: Anuradhapura, a rural district in Sri Lanka. Participants: A representative sample of 1096 patients with CKD, selected using the population-based CKD register, completed the EQ-5D-3L and SF-36. SF-6D was constructed from the SF-36 according to the published algorithm. The study assessed discrimination, correlation and differences across the two instruments. Results: Study participants were predominantly male (62.6%). Mean EQ-5D-3L utility score was 0.540 (SD 0.35) compared with 0.534 (SD 0.09) for the SF-6D (p=0.588). The correlation (r) between the scores was 0.40 (p<0.001). Utility scores were significantly different in both males and females between the two tools, but there was no difference in age and educational categories. Both MAUI scores were significantly lower (p<0.001) among those who were in more advanced stages of the disease and the corresponding utility scores of the two instruments in different CKD stages were also significantly different (p<0.05). The largest effect size was seen among the patients on dialysis. Conclusions: The correlation between the scores was moderate. SF-6D had the lowest floor and ceiling effect and was better at detecting different stages of the disease. Thus, based on the evidence presented in this study, SF-6D appears to be more appropriate to be used among patients with CKD.